Case Report: Amiodarone-induced multi-organ toxicity - Yan, Jingrui; Xu, Yuanyuan; Zhu, Qiang (Frontiers in Cardiovascular Medicine, 2024)
Background: Amiodarone is a class III antiarrhythmic drug that is commonly used in the clinic to treat ventricular arrhythmias and atrial fibrillation. We present a case report of the adverse effects of amiodarone and review its characteristics. Case report: A 73-year-old Asian female with a history of paroxysmal atrial fibrillation managed with amiodarone, well-controlled hypertension, and no substance abuse presented with gastrointestinal distress and dizziness, without chest pain or palpitations. Despite normal annual check-ups, she developed abnormal liver and thyroid function tests, and imaging revealed lung and liver changes suggestive of amiodarone toxicity. Discontinuation of amiodarone for sotalol led to symptom improvement and normalization of thyroid and liver functions, with imaging indicating recovery from interstitial fibrosis and reduced liver density. Discussion: Amiodarone, a widely used for treating ventricular and atrial arrhythmias, and with significant benefits in improving patient survival in cases of ventricular fibrillation. However, its long-term use is associated with serious adverse effects, including thyroid dysfunction, liver injury, and pulmonary toxicity, necessitating careful monitoring and management. Despite its efficacy, the need for research on early detection and management of amiodarone's side effects is crucial, highlighting the importance of regular monitoring and possibly adjusting therapy to mitigate these risks.